2015
DOI: 10.1111/liv.12781
|View full text |Cite
|
Sign up to set email alerts
|

TM6SF2 E167K variant is associated with severe steatosis in chronic hepatitis C, regardless of PNPLA3 polymorphism

Abstract: This is the first demonstration that TM6SF2 E167K variant is an independent predictor of liver steatosis in chronic hepatitis C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 24 publications
0
58
0
3
Order By: Relevance
“…The analysis included a total of 4187 subjects from which the values of ALT according to E167K genotypes could be extracted15161718; this sample included 3680 patients with HCV and 507 patients with HBV. Only two studies reported data on AST levels1516.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis included a total of 4187 subjects from which the values of ALT according to E167K genotypes could be extracted15161718; this sample included 3680 patients with HCV and 507 patients with HBV. Only two studies reported data on AST levels1516.…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies reported data on AST levels1516. The mean value of ALT and AST according to genotypes of the dominant model of rs58542926 in each study is disclosed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…5, 9, 10, 17, 3437 More recently, the same variant in the TM6SF2 gene has been identified as a novel risk locus for alcohol-related cirrhosis in the European descent and validated in two independent European cohorts. 38 The global Tm6sf2 KO mice and liver-specific transgenic mice allowed us to determine the long-term effect of TM6SF2 on lipid metabolism in the liver.…”
Section: Discussionmentioning
confidence: 96%
“…In fact, a recent study on chronic hepatitis C showed that while TM6SF2-E167K variant is an independent predictor of liver, no difference in necroinfl ammatory or fi brosis scores was found among carriers and noncarriers of the risk allele [ 51 ]. Finally, functional studies on TM6SF2 gene demonstrated that this locus and the mentioned variant are relevant on NAFLD disease biology.…”
Section: Gwas On Nafld and The Genetic Risk Of Disease Progressionmentioning
confidence: 95%